2004
DOI: 10.1007/s00223-003-0068-7
|View full text |Cite
|
Sign up to set email alerts
|

Osteonecrosis in a Chemically Induced Rat Model of Human Hemolytic Disorders Associated with Thrombosis ? A New Model for Avascular Necrosis of Bone

Abstract: Bone injury occurs in human hemolytic disorders associated with thrombosis, such as beta-thalassemia and sickle cell disease. Exposure of rats to 2-butoxyethanol (BE) has been associated with hemolytic anemia, disseminated thrombosis, and infarction in multiple organs including bone. This rat model apparently mimics acute hemolysis and thrombosis in humans. To elucidate the extent of bone injury, male and female Fischer F344 rats were given 4 daily doses of 250 mg BE/5 ml water/kg of body weight. Tail vertebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Metabolic activation of 2-butoxyethanol (BE) to form butoxyacetic acid (BAA) is a prerequisite for the development of hematotoxicity. Shabat et al [77] reported a new rat model for ON induced by four daily doses of 250 mg BE/5 ml water/kg of body weight for four consecutive days. At 24 days after induction, ON in femur was seen histologically in 1 of 8 animals while changes in the femurs were confined to the diaphysis.…”
Section: Chemically Induced Onmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic activation of 2-butoxyethanol (BE) to form butoxyacetic acid (BAA) is a prerequisite for the development of hematotoxicity. Shabat et al [77] reported a new rat model for ON induced by four daily doses of 250 mg BE/5 ml water/kg of body weight for four consecutive days. At 24 days after induction, ON in femur was seen histologically in 1 of 8 animals while changes in the femurs were confined to the diaphysis.…”
Section: Chemically Induced Onmentioning
confidence: 99%
“…Bone injury occurs in human hemolytic disorders associated with thrombosis, such as betathalassemia and sicklecell disease [77]. Metabolic activation of 2-butoxyethanol (BE) to form butoxyacetic acid (BAA) is a prerequisite for the development of hematotoxicity.…”
Section: Chemically Induced Onmentioning
confidence: 99%
“…Cessation or a reduction in blood flow along capillaries could also play an aetiological role in endothelial cell apoptosis. 59 – 61…”
Section: Endothelial Cell Apoptosismentioning
confidence: 99%